Quantitative assessment of seismic source performance: Feasibility of small and affordable seismic sources for long term monitoring at the Ketzin CO2 storage site, Germany - Sopher, D.; Juhlin, Christopher; Huang, F.; Ivandic, M.; Lueth, S. (Elsevier, 2014)
We apply a range of quantitative pre-stack analysis techniques to assess the feasibility of using smaller and cheaper seismic sources, than those currently used at the Ketzin CO2 storage site. Results from two smaller land sources are presented alongside those from a larger, more powerful source, typically utilized for seismic acquisition at the Ketzin. The geological target for the study is the Triassic Stuttgart Formation which contains a saline aquifer currently used for CO2 storage. The reservoir lies at a depth of approximately 630m, equivalent to a travel time of 500ms along the study profile. The three sources discussed in the study are the Vibsist 3000, Vibsist 500 (using industrial hydraulic driven concrete breaking hammers) and a drop hammer source.Data were collected for the comparison using the three sources in 2011, 2012 and 2013 along a 984m long line with 24m receiver spacing and 12m shot spacing. Initially a quantitative analysis is performed of the noise levels between the 3 surveys. The raw shot gathers are then analyzed quantitatively to investigate the relative energy output, signal to noise ratio, penetration depth, repeatability and frequency content for the different sources. The performance of the sources is also assessed based on stacked seismic sections. Based on the results from this study it appears that both of the smaller sources are capable of producing good images of the target reservoir and can both be considered suitable as lower cost, less invasive sources for use at the Ketzin site or other shallow CO2 storage projects. Finally, the results from the various pre-stack analysis techniques are discussed in terms of how representative they are of the final stacked sections. © 2014.